2011
DOI: 10.1186/1756-0500-4-207
|View full text |Cite
|
Sign up to set email alerts
|

Mammograms and breast arterial calcifications: looking beyond breast cancer: a preliminary report

Abstract: BackgroundTo find out the prevalence, clinical and biochemical correlates of Breast Artery Calcification (BAC) in the Nigerian women.FindingsThis is a cross sectional study involving 54 consecutive adult female subjects sent to the Radiology Department of the Lagos State University Teaching Hospital (LASUTH), Ikeja-Lagos, Nigeria for screening and diagnostic mammography. The study was carried out for a period of five months.The prevalence of BAC was 20%. Ageing was found to be related to BAC. Cardiovascular ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
2
8
3
Order By: Relevance
“…In keeping with the findings of Bielak et al (34) , Zafar et al (35) , and Akinola et al (36) , we found no correlation between obesity and BAC in our study sample. It is also noteworthy that we found no correlation between smoking and BAC, which is in line with the findings of Almeida et al (37) and Iribarren et al (33) .…”
Section: Discussionsupporting
confidence: 93%
“…In keeping with the findings of Bielak et al (34) , Zafar et al (35) , and Akinola et al (36) , we found no correlation between obesity and BAC in our study sample. It is also noteworthy that we found no correlation between smoking and BAC, which is in line with the findings of Almeida et al (37) and Iribarren et al (33) .…”
Section: Discussionsupporting
confidence: 93%
“…Some studies show a significant association between BAC and hypertension, 19,32,33 whereas others show no such association. 4,24,34 Similarly, with diabetes mellitus, some studies show a statistically significant association, 6,19,35,36 whereas others show none. 4,24,37,38 …”
Section: Discussionmentioning
confidence: 98%
“…4 Calcifications of mammary arteries frequently represent age-related degenerative changes; 5 their incidence increases with age, and they are uncommon in mammograms performed in women less than 50 years of age.…”
mentioning
confidence: 99%
“…In the literature so far, the prevalence of BAC on mammography has been reported at very different frequencies (21). The prevalence of BAC varies from 1% to 49% in previous studies (21)(22)(23)(24)(25)(26)(27)(28). Such a significant difference in prevalence may be explained by variations in sensitivity of mammography equipment and the heterogeneity of the study groups (16).…”
Section: A B a Bmentioning
confidence: 98%